2006
DOI: 10.1111/j.1475-1313.2006.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mallett Fixation Disparity Test: influence of test instructions and relationship with symptoms

Abstract: Fixation disparity is a minute ocular misalignment under conditions of binocular single vision and is typically detected in primary eye care practices in the UK using the Mallett Unit Fixation Disparity Test. This instrument creates natural viewing conditions, when the patient's binocular system is fused using both central and peripheral fusion locks. This allows the examiner to determine the minimum prism power that eliminates the fixation disparity: the associated phoria or aligning prism. The spherical powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 72 publications
2
50
3
Order By: Relevance
“…Future studies should therefore include a system which grades both the quantity and severity of symptoms using a validated symptom questionnaire. It is of interest to note however that despite these limitations the present data again supports the findings from earlier research which suggests that an aligning prism reported in the distance is not a good predictor of binocular vision symptoms suggestive of a decompensating heterophoria [7][8], [26][27]. In fact the only research to support the use of the Mallett Unit in the distance, reported that correction of the associated phoria resulted in an improvement the equivalent of one half of a line on the Snellen chart (approximately 0.05 logMAR) [22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Future studies should therefore include a system which grades both the quantity and severity of symptoms using a validated symptom questionnaire. It is of interest to note however that despite these limitations the present data again supports the findings from earlier research which suggests that an aligning prism reported in the distance is not a good predictor of binocular vision symptoms suggestive of a decompensating heterophoria [7][8], [26][27]. In fact the only research to support the use of the Mallett Unit in the distance, reported that correction of the associated phoria resulted in an improvement the equivalent of one half of a line on the Snellen chart (approximately 0.05 logMAR) [22].…”
Section: Discussionsupporting
confidence: 86%
“…Both units contain a central fusion lock which is known to be important when measuring aligning prism [18][20]. All patients received instructions to carry out the test based on recommendations by Karania & Evans (2006) [8] as it has been shown that appropriate instructions result in more likelihood of picking up symptomatic patients. A prism bar cover test was performed using a Gulden prism bar (Gulden Ophthalmics) at a distance of 6 m and 40 cm to measure the heterophoria at distance and near respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] About 20% of patients who come to optometry clinics will have binocular vision anomalies or decompensated heterophoria. [2] Due to the high prevalence of binocular vision anomalies, a regular vision examination is advisable for identification of these disorders. Convergence function is evaluated with clinical tests to determine whether the visual system can provide the patient's vergence needs at near.…”
mentioning
confidence: 99%
“…The magnitude and direction of prism required to null apparent target movement was taken as the phoria value. Specifically, a prism bar was used to incrementally add prism power until the subject reported a reversal of movement direction (prism bar values were 1, 2, 4, 6,8,10,12,14,16,18,20,25,30,35,40, and 45 prism diopters). Prism power was then reduced until the subject reported a second reversal.…”
Section: Phoriamentioning
confidence: 99%